Lyophilized artificial diet for rearing the Neotropical Euschistus heros (Hemiptera: Pentatomidae) - Mendoza, Agustín C. (J Insect Sci, 2016)
An artificial diet to mass-rear Euschistus heros (F. 1798) (Hemiptera: Pentatomidae) was developed in the laboratory. Biological studies were conducted under controlled conditions of temperature (25 ± 2°C), RH: 60 ± 10%, and photoperiod of 14:10 (L:D) h. Out of 13 diets tested, 2 diets (D9 and D11) were the most suitable. The artificial diets selected had the same composition (green beans, peanuts, sucrose, water, Nipagin, and sorbic acid) except for different antimicrobial agents (D11 has tetracycline, and D9 doesn’t). The 68% viability for the egg–adult period of insects reared on these lyophilized artificial diets (LAD) was almost twice as high as the 38% viability obtained with the natural diet. Although adults reared on LAD weighed 17% less than those reared on the natural diet, mean fecundity was higher than on the natural diet (282 eggs/female), reaching 430 eggs/female. The net reproductive rate (Ro) increased over the generations for the diets with lyophilized material and antimicrobial agents. The opposite occurred with the diet of lyophilized material without antimicrobial agents, showing that the insects either adapted or degenerated through generations. Lyophilized diets supported the production of E. heros through at least 10 generations, with no degeneration.